Searching the Literature on Scholarship of Teaching and Learning (SoTL): An Academic Literacies Perspective: Part 1 - Healey, Mick; Healey, Ruth L. (Teaching and Learning Inquiry, 2023)
There are few references that critically evaluate the different ways of searching the literature on scholarship of teaching and learning (SoTL), or how these are related to researchers’ goals. We use an academic literacies perspective as a lens with which to explore the different ways that literature searches may be undertaken. While searching the literature is often presented as a scientific objective process, the reality is much messier, nuanced, and iterative. It is a complex, context-dependent process. We provide a practical, critical guide to undertaking SoTL literature searches and argue that these need to be seen as socially constructed processes. There is no one right way of searching the SoTL literature. The academic literacies perspective leads us to emphasise the variety of different purposes for carrying out a literature search. We distinguish between using comprehensive tools and selective sources. We end by arguing that there is a need for SoTL researchers to be less insular and take purposeful steps to search for, cite, and amplify diverse voices. This article complements a separate one where we review and synthesise the SoTL literature. Click here to read the corresponding ISSOTL blog post.